Relapse in teenage and young adult patients treated on a paediatric minimal residual disease stratified ALL treatment protocol is associated with a poor outcome: results from UKALL2003. (24th April 2018) - Sellar, Rob S.; Rowntree, Clare; Vora, Ajay J.; Furness, Caroline L.; Goulden, Nicholas; Mitchell, Chris; Moorman, Anthony V.; Hough, Rachael
Abstract: Outcomes for teenage and young adult (TYA) patients with acute lymphoblastic leukaemia (ALL) who relapse on contemporary risk‐adapted paediatric protocols are largely unknown and there is no consensus on optimal salvage strategies. We assessed the treatment and outcome of TYA patients (aged 16–24 years) recruited to the UKALL2003 trial, who relapsed following attainment of complete morphological remission. Forty‐two of 223 patients (18·8%) relapsed, the majority ( n  = 26, 62%) on treatment. Thirty‐eight (90%) patients received salvage treatment, with 22 (58%) achieving second remission (CR2) and 21 patients receiving an allogeneic haematopoietic cell transplant (alloHSCT). Post‐relapse outcomes were poor with a 5‐year overall survival (OS) of 23% (95% confidence interval; 11–37%). Outcomes for patients relapsing on active treatment were inferior to those relapsing after completing treatment (5‐year OS 9% vs. 52%, log‐rank P  = 0·001). No patient with B cell ALL relapsing on treatment was alive at the end of the study period. TYA patients with ALL who relapse on the UK paediatric protocol, UKALL2003, are largely unsalvageable with conventional approaches aimed at achieving CR2 followed by alloHSCT. Future efforts should be aimed at identifying those patients who are destined to relapse and exploring novel treatment approaches for this high‐risk group and for those who do relapse.